2018
DOI: 10.1021/acschemneuro.7b00477
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Rational Design to Regulate β-Amyloid Fibrillation for Alzheimer’s Disease Treatment

Abstract: The last decades have witnessed a growing global burden of Alzheimer's disease (AD). Evidence indicates that the onset and progression of AD is associated with β-amyloid (Aβ) peptide fibrillation. As such, there is a strong passion with discovering potent Aβ fibrillation inhibitors that can be developed into anti-amyloiddogenic agents for AD treatment. Current challenges that have arisen with this development involve with Aβ oligomer toxicity suppression and Blood Brain Barrier penetration capability. Consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 99 publications
0
70
0
Order By: Relevance
“…The most common fibrils are Aβ(1–40) and Aβ(1–42), which are composed of 40 and 42 amino acids, respectively, and are characterized by β-strand units aligned perpendicularly to the main fibril axis [ 2 ]. Destabilization and clearance of amyloid aggregates by small molecules is one of the promising approaches towards the development of AD therapies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common fibrils are Aβ(1–40) and Aβ(1–42), which are composed of 40 and 42 amino acids, respectively, and are characterized by β-strand units aligned perpendicularly to the main fibril axis [ 2 ]. Destabilization and clearance of amyloid aggregates by small molecules is one of the promising approaches towards the development of AD therapies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The solvation energy, Gsolvation, is calculated as follows: (4) Where the non-polar solvation term, Gsurf, is approximated on the solvent-accessible-surface area (SASA) derived from the Shrake-Rupley numerical method [45] (5) with γ=0.0072kcal/mol Å 2 and β=0 [46].…”
Section: Ligand Binding Energymentioning
confidence: 99%
“…The most common fibrils are Aβ and Aβ that are composed by 40 and 42 amino acids, respectively, and are characterized by β-strand units aligned perpendicular to the main fibril axis [2]. Destabilization and clearance of amyloid aggregates by small molecules is one of the promising approaches towards the development of AD therapies [4].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, BuChE inhibitors could recover cholinergic activity through restoring the AChE/BuChE activity ratios, as shown in a healthy brain [ 8 ], and BuChE may play a role in AD plaque due to its contribution to a subpopulation of Aβ plaques maturation by immunostaining analysis of AD brain tissues [ 9 ]. Nevertheless, many studies have showed that both ChEs could facilitate amyloid fibril formation to yield stable ChE-Aβ complexes, which are more toxic than a single Aβ peptide [ 10 , 11 ]. The complex of AChE, through interaction with Aβ, promotes amyloid fibril formation through a spanning hydrophobic sequence exposed on the surface of AChE, which is close to the peripheral anionic binding site (PAS) and interacts with liposomes.…”
Section: Introductionmentioning
confidence: 99%